The effects of knowledge management and risk taking on SME financial performance in creative industries in an emerging market: The mediating effect of innovation outcomes - Donard Games; Ranggi Putri Rendi; Hazeline Ayoup (Journal of Global Entrepreneurship Research, 2019)
The purpose of the present study is to examine the effects of knowledge management and risk taking on financial performance in which negative innovation outcomes was chosen as a mediator variable. The present study uses the context of small and medium enterprises (SMEs) in creative industries in Indonesia which is an emerging market economy. Based on an analysis of data from 165 small business owners in creative industries in Indonesia, the present study found some interesting notion regarding SME innovation. The results of this study indicate the importance of knowledge management and risk taking as ways of reducing negative innovation outcomes. Further, it was found that negative innovation outcomes did not mediate the links between knowledge management, risk taking, and SME financial performance. The present study offers some insights from Indonesia as an emerging market economy which may have different characteristics compared to other contexts. Risk taking represents a clear growth path to enhance SME financial performance. This is partly because Indonesia as an emerging market with a collectivist culture may encourage SMEs to be more open to changes and social networks that enhance knowledge management, and more importantly new ways of doing business. The present study uses negative innovation outcomes and SME financial performance to indicate whether SMEs in an emerging market economy can benefit from business innovation.
Keywords: 650; Knowledge management; Risk taking; SME innovation; Emerging markets; Indonesia; Innovation outcomes; SME financial performance